Tracing the Cambro-Ordovician ferrosilicic to calc-alkaline magmatic - Diaz-Alvarado, Juan (2017)
U–Pb geochronological study of zircons from nodular granites and Qtz-diorites comprising part of Variscan high- grade metamorphic complexes in Gredos massif (Spanish Central System batholith) points out the significant presence of Cambro-Ordovician protoliths among the Variscan migmatitic rocks that host the Late Carboniferous intrusive granitoids. Indeed, the studied zone was affected by two contrasted tectono-magmatic episodes, Car- boniferous (Variscan) and Cambro-Ordovician. Three main characteristics denote a close relation between the Cambro-Ordovician protholiths of the Prado de las Pozas high-grade metamorphic complex, strongly reworked during the Variscan Orogeny, and other Cambro-Ordovician igneous domains in the Central Iberian Zone of the Iberian Massif: (1) geochemical features show the ferrosilicic signature of nodular granites. They plot very close to the average analysis of themetavolcanic rocks of the Ollo de Sapo formation (Iberia). Qtz-diorites present typical calc-alkaline signatures and are geochemically similar to intermediate cordilleran granitoids. (2) Both Qtz-diorite and nodular granite samples yield a significant population of Cambro-Ordovician ages, ranging between 483 and 473 Ma and between 487 and 457 Ma, respectively. Besides, (3) the abundance of zircon inher- itance observed on nodular granites matches the significant component of inheritance reported on Cambro- Ordovician metagranites and metavolcanic rocks of central and NW Iberia. The spatial and temporal coincidence of both peraluminous and intermediate granitoids, and specifically in nodular granites and Qtz-diorite enclaves of the Prado de las Pozas high-grade complex, is conducive to a common petrogenetic context for the formation of both magmatic types. Tectonic and geochemical characteristics describe the activity of a Cambro-Ordovician arc-back-arc tectonic set- ting associated with the subduction of the Iapetus–Tornquist Ocean and the birth of the Rheic Ocean. The exten- sional setting is favorable for the generation, emplacement, and fast rise of subduction-related cold diapirs, supported by the presence of typical calc-alkaline cordilleran granitoids contemporary with ferrosilicic volcanism.